Children's Quranic Literacy as the Foundation of Family Spiritual Resilience - Zaeni Dahlan; Eva Siti Faridah; Siskha Putri Sayekti; Munakhiroh El-Hajar; Isep Djuanda (Al-Qalam Institute, 2025)
This study examines how children’s Quranic literacy functions as the foundation of family spiritual resilience at Al-Quran education park (TPA). Family resilience as a multidimensional capacity to manage stress and maintain well-being, while other research highlights spirituality as a protective factor in coping with life challenges. However, limited attention has been given to how children’s Quranic literacy operates as a systemic mechanism that strengthens spiritual resilience within family contexts. A qualitative case study approach was employed, involving observations, in-depth interviews with teachers and parents, and documentation analysis. Data were analyzed through thematic coding to identify patterns linking Quranic literacy practices with family spiritual dynamics. The findings reveal the emergence of a Participatory Quranic Learning Framework that integrates children, teachers, and parents in structured religious engagement. Children’s Quranic literacy was found to function as a cognitive-spiritual foundation by fostering moral reasoning, emotional regulation, and meaning-making capacities. Furthermore, the benefits of Quranic literacy extend to strengthening family communication, reinforcing shared values, and enhancing collective coping strategies. This study contributes a conceptual model linking Quranic literacy with family resilience and recommends integrating family-based participatory approaches into community Quran education programs.